Strengthening Student Character Education in Forming Noble Morals through School Culture: Penguatan Pendidikan Karakter Siswa dalam Membentuk Akhlak Mulia melalui Kultur Sekolah - Nurasih, Rita; Putriani, Mustika; Yudhistira, Raffi Audi; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2024)
This article aims to examine strengthening student character education in forming noble morals through school culture. This study is based on the implementation of character strengthening that has been developed in elementary schools, but has not shown optimal results. One of the causes is the implementation of character education which runs partially and focuses only on classroom learning. The implementation of character education in schools should be comprehensive, meaning that the program must be supported by activities outside the classroom which include extra-curricular co-curricular programs and the development of school culture. Character education through developing school culture is carried out using two approaches, namely the structural and cultural approaches. The implementation of character education based on school culture is implemented using modeling, teaching and environmental strengthening strategies. Character education can be effective and successful if it is carried out integrally starting from the household, school and community environment. Characters that must be instilled in students include love for Allah and the universe, responsibility, discipline and independence, honesty, respect and politeness, compassion, caring and cooperation, self-confidence, creativity, hard work and never giving up, justice and leadership, kindness and humility, tolerance, love, peace and unity. Meanwhile, noble morals are all human habits that originate within the self which are driven by conscious desire and are reflected in good deeds.